2021
DOI: 10.3233/nha-200098
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting - a potential approach to modulate the gut microbiota in humans? A systematic review

Abstract: Research on gut microbiota has increased in popularity over the past decade, with evidence associating different dietary habits with changes in the makeup of the rich ecosystem of microorganisms that performs a variety of functions and induces a range of health effects, within and well beyond the gastrointestinal tract. Similarly, intermittent fasting (IF), an umbrella term describing various regimens of periods of voluntary abstinence from food and drink, has classically been associated with favourable impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…29 Relatively few human studies have been performed to assess IF-induced changes in gut microbiota and the relationship with weight loss and host metabolism, and even for these few studies, only the 16S rRNA gene amplicon sequencing approach was applied, hampering analyses at the species level. 29,30 In this study, we observed that the relative abundances of multiple Bacteroides and Parabacteroides species, especially the known bene cial bacteria P. distasonis and B. thetaiotaomicron, were signi cantly increased after the IF intervention. This change is different from what has been reported in previous mouse studies, underscoring the differences between the mouse and the human gut microbiota, suggesting that the responses to IF interventions and the related molecular mechanisms may differ.…”
Section: Discussionmentioning
confidence: 64%
“…29 Relatively few human studies have been performed to assess IF-induced changes in gut microbiota and the relationship with weight loss and host metabolism, and even for these few studies, only the 16S rRNA gene amplicon sequencing approach was applied, hampering analyses at the species level. 29,30 In this study, we observed that the relative abundances of multiple Bacteroides and Parabacteroides species, especially the known bene cial bacteria P. distasonis and B. thetaiotaomicron, were signi cantly increased after the IF intervention. This change is different from what has been reported in previous mouse studies, underscoring the differences between the mouse and the human gut microbiota, suggesting that the responses to IF interventions and the related molecular mechanisms may differ.…”
Section: Discussionmentioning
confidence: 64%
“…Other mouse studies have investigated the changes in gut microbiota induced by different dietary fasting programs but rarely reported on significant change in the relative abundance of Bacteroides or Parabacteroides 29 . Relatively few human studies have been conducted to assess IF-induced changes in the gut microbiota and the relationship with weight loss and host metabolism, and even for these few studies, only the 16S rRNA gene amplicon sequencing approach was applied, hampering analyses at the species level 29 , 30 . These studies reported that ADF and Ramadan would lead to an increase in the relative abundance of Bacteroidaceae and Bacteroides in multiple sclerosis patients and healthy adults, respectively 31 , 32 , whereas other reported that IF-induced changes in taxonomic composition of gut microbiota were not consistent in published articles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent review articles have summarized human trials concerning IF and its effects on the gut microbiota 29 , 30 . As a significant advantage of the current study, deep metagenomic sequencing and de novo assembly, rather than 16S rRNA gene amplicon sequencing, were performed providing information regarding the gut microbiota at the level of species or even strains, as well as information regarding the functional potential.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reviews have summarized the effects of IF on the gut microbiota [ 304 , 305 ] ( Figure 4 ). In healthy mice, one month of ADF intervention led to an increase Lactobacillaceae , Bacteroidaceae , and Prevotellaceae family bacteria, whereas one month of 16-hour TRF was linked with an increase in A. muciniphila and a decrease in Alistipes genus bacteria [ 306 , 307 ].…”
Section: Dietary Interventions That Act On Body Weight and That Shape...mentioning
confidence: 99%